Dynamics and elasticity of the fibronectin matrix in living cell culture visualized by fibronectin–green fluorescent protein - Ohashi, Tomoo (The National Academy of Sciences, 1999)
Fibronectin (FN) forms the primitive fibrillar matrix in both embryos and healing wounds. To study the matrix in living cell cultures, we have constructed a cell line that secretes FN molecules chimeric with green fluorescent protein. These FN–green fluorescent protein molecules were assembled into a typical matrix that was easily visualized by fluorescence over periods of several hours. FN fibrils remained mostly straight, and they were seen to extend and contract to accommodate movements of the cells, indicating that they are elastic. When fibrils were broken or detached from cells, they contracted to less than one-fourth of their extended length, demonstrating that they are highly stretched in the living culture. Previous work from other laboratories has suggested that cryptic sites for FN assembly may be exposed by tension on FN. Our results show directly that FN matrix fibrils are not only under tension but are also highly stretched. This stretched state of FN is an obvious candidate for exposing the cryptic assembly sites.